Pharmacological Basis of Acute Care - Chan, Yoo Kuen; Ng, Kwee Peng; Sim, Debra Si Mui (Springer eBooks, 2015)
This book is the 4th in a series of Acute Care books written with the aim to address the NEEDS of health care providers when handling the acutely ill patients. Globally it has become apparent that the study of pharmacology and subsequent clinical training has not always adequately equipped young doctors with the ability to administer drugs to their patients safely and confidently, particularly in the critically ill patient. Compounding this issue is the lack of resource material related to these pharmacological concepts contained in one book that can help health care providers to understand and manage drug therapy in the acute situation. In spite of progressively newer and more developed  protocols, guidelines, algorithms and many other books addressing the technical aspects of what needs to be done, most health care providers still find it difficult to grasp the basic pharmacological knowledge and rationally deliver the CARE that is required in the acute phase of patient management. The editors/authors have therefore aimed for a book that highlights topics and pharmacological issues pertinent to management of patients in their hour of need. This is a multi-author book but the style has been guided by 3 editors. The editors have used a different perspective – that of normalizing abnormal physiological processes with pharmacological agents – to address the GAPS in a bedside to bench approach. The details are pared down but important principles/concepts are emphasized.